Group Investigation Learning Implementation and EAOAT-Based Assessement on Profession Education Subject - Krisna Merdekawati (IJCER (International Journal of Chemistry Education Research), 2017)
ABSTRACT: Profession Education subject has wide coverage lecture material and tend to be regarded as a theoretical matter. Profession Education conventionally, students will only examine theoretically and less meets the subject goals. Evaluation shows that it needs improvement efforts from material aspects, strategies, and assessment systems in Profession Education lectures. The study focused on the description of the implementation and effect of GI in Professions Education subject, a description of EOOAT-based assessment implementation. Subjects of this study were students of Chemical Education Islamic University of Indonesia who took Profession Education subject in the academic year 2016/2017. Lectures conducted with the collaboration of lecturers and expert lecturers from National University of Malaysia. The research instruments include course outline, lecture events unit, hand outs, diagnostic tests, project assessment, cognitive assessment, self-assessment, student satisfaction questionnaires, and expert lecturer’s assessment questionnaire. Lectures conducted in accordance with the stages in the GI, namely: identification of topics, planning investigations, execution of investigations, preparation of the final report, presentation of the final report, an evaluation of progress. Oriented learning outcomes should ideally use a rating system that can give a continuous process and performance. With EOOAT-based assessment, teachers can determine the difficulties and competencies that have not reached by the students. Lecturers can further specify corrective measures in learning to allow students to achieve competence expected. Data research shows that GI learning and EOOAT-based learning has a positive impact. The final grade point average of students was 79.2. The average score of student satisfaction was 92.5. The expert lecturer’s assessment scores were 95.8. From self assessment showed that students understand the lecture material and the interest in the teacher profession was increased after the lecture.Keywords: group investigation, EAOAT assessment, profession educationReceived: 15 June 2017, Revised: 4 August 2017, Accepted: 1 September 2017